1991
DOI: 10.1152/ajpheart.1991.261.4.h1086
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase recovers altered endothelium-dependent relaxation in diabetic rat aorta

Abstract: Experiments were designed to characterize endothelium-dependent relaxation in thoracic aortic rings obtained from streptozotocin-induced diabetic rats. When the degree of the peak relaxation was compared, the endothelium-dependent relaxant responses to acetylcholine, histamine, or ADP in precontracted aortic rings showed that there was no significant difference between diabetic and control vessels. However, the time courses appeared quite different. The endothelium-dependent relaxant responses in diabetic vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
139
1
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(159 citation statements)
references
References 0 publications
13
139
1
6
Order By: Relevance
“…Decreased endothelial-dependent relaxation, a common assay for ED in aortic rings (37)(38)(39) and mesenteric microvessels (40,41), indicates that both conductance and resistance vessels are affected. In the diabetic mesentery the vascular tree undergoes hypertrophy preceded by attenuated endothelial dependent relaxation (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased endothelial-dependent relaxation, a common assay for ED in aortic rings (37)(38)(39) and mesenteric microvessels (40,41), indicates that both conductance and resistance vessels are affected. In the diabetic mesentery the vascular tree undergoes hypertrophy preceded by attenuated endothelial dependent relaxation (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of such an action of vasoconstrictor prostanoids in the kidney is not supported by our study, inasmuch as cyclooxygenase-inhibition did not restore the blunted relaxations observed in the diabetic animals. Other investigations showed an impaired acetylcholine-induced cyclic GMP generation [7,8] or a restoration of the relaxation with l-arginine [9] or with free radical scavengers [10,11], suggesting a reduced availability or an increased destruction of endotheliumderived NO. Another study specifically found no evidence for an impaired EDHF release in diabetes [34].…”
Section: Basalmentioning
confidence: 99%
“…It has been suggested that the excessive elevations in plasma glucose, insulin, low density lipoprotein (LDL) cholesterol, endothelin-1 (ET-1), Ang II, and reactive oxygen species that occur in diabetes are involved in the development of this dysfunction in several blood vessels. Indeed, a considerable body of evidence now suggests that in type I diabetes, the observed impairment of endothelial function may involve inactivation of NO by oxygen-derived free radicals (Meraji et al, 1987;Hattori et al, 1991;Pieper et al, 1992;Tesfamariam, 1994;Keaney and Vita, 1995;Kamata et al, 1996a;Ooboshi et al, 1997;Kobayashi and Kamata, 1999a, 2002b. In experimental models of type I diabetes, an enhancement of NO production (which in such models is diminished by superoxide anion) and dismutation of free radicals has generally been found to improve impaired endothelium-dependent relaxation (Rubanyi and Vanhoutte, 1986;Marshall et al, 1988;Kobayashi and Kamata, 2001).…”
Section: Mechanisms Underlying Impaired Endothelial Function In Diabementioning
confidence: 99%